Influence of Removable Devices' Heterouse on the Propagation of Malware. (13th November 2013) - Han, Xie; Li, Yi-Hong; Feng, Li-Ping; Song, Li-Peng
Abstract : The effects of removable devices' heterouse in different areas on the propagation of malware spreading via removable devices remain unclear. As a result, in this paper, we present a model incorporating the heterogeneous use of removable devices, obtained by dividing the using rate into local area's rate, neighbour area's rate and global area's rate, and then getting the final rate by multiplying the corresponding area ratio. The model's equilibria and their stability conditions are obtained mathematically and verified by deterministic and stochastic simulations. Simulation results also indicate that the heterogeneity in using rate significantly changes the prospective propagation course of malware. Additionally, the thresholds of removable devices' using rate in neighbour area are given, which can guide us in designing effective countermalware method.